Cortes, provincias o reinos… ¿qué hacer con las Indias occidentales? Los proyectos «constitucionales» de monarquías americanas (siglos XVI-XIX) - Ciaramitaro, Fernando (2024)
In recent years, the court has been a relevant topic in historiography. When we refer to the court as a space that is political, artistic, financial, etc., we should not only think of the court par excellence, that of the king, but also of the other distinct spheres made up of nobles, ecclesiastics and illustrious members of the common folk, who formed centers of scholarly discussion and power and exercised a political, religious, cultural and economic role in the territory. In the Indies, different courts were juxtaposed with each other, but researchers have tended to focus on viceregal courts. In these courts, the highest monarchical office was executed: the viceroy acted as the link between the monarch and his American vassals, and as an impressive focal point for groups that composed the sociopolitical framework of the viceroyalties. The court was the most prestigious center in which guidelines, ideologies, and symbols were developed, all of which were elements that comprised the essence or core of power. The objective of this study is therefore to analyze the main plans that, from the court of the monarch in Spain and the Indies, were drawn for the Americas: theoretical designs that did not become fact. They are, nonetheless, valuable for understanding the changes in political thought and law, throughout the 16th, 17th and 18th centuries.